Cartilage Graft Donor Site Morbidity following Rhinoplasty and Nasal Reconstruction. Issue 4 (December 2018) - Ho, Thuy-Van Tina; Sykes, Kevin; Kriet, J.David; Humphrey, Clinton
Although surgical techniques for rhinoplasty and nasal reconstruction are well established, prospective research on postoperative morbidity remains limited. The aim of this pilot study was to assess costal and auricular cartilage donor site pain and morbidity in patients undergoing rhinoplasty and nasal reconstruction. In this prospective cohort study, we enrolled 55 patients undergoing nasal surgery that required costal or auricular cartilage harvest from February 2015 through May 2016. Each patient was given a symptom-specific patient survey that assessed general pain, nasal pain, graft donor site pain, graft donor site itching, color variation, skin stiffness and thickness, and graft donor site appearance at 1, 4, and 12 weeks after surgery. Our patient group was 55% female ( n = 30); the mean age was 47 years. Rib cartilage graft patients had significantly greater nasal pain than cartilage donor site pain. There was no significant difference in rib versus ear cartilage donor site pain. Nearly all patients reported that they were not at all concerned about their scar appearance or ear shape and appearance. No prior studies compare cartilage donor site morbidity in patients undergoing nasal surgery. Our findings challenge the conventional wisdom that utilizing auricular and costal cartilage results in high levels of donor site pain. Surgeons should have a low threshold to harvest rib or ear cartilage when it can improve surgical outcome.